2015
DOI: 10.1016/j.yjmcc.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic automaticity induced in ventricular myocytes by transgenic overexpression of HCN2

Abstract: Hyperpolarization-activated cyclic nucleotide-gated channels (HCNs) are expressed in the ventricles of fetal hearts but are normally down-regulated as development progresses. In the hypertrophied heart, however, these channels are re-expressed and generate a hyperpolarization-activated, nonselective cation current (Ih), which evidence suggests may increase susceptibility to arrhythmia. To test this hypothesis, we generated and analyzed transgenic mice overexpressing HCN2 specifically in their hearts (HCN2-Tg).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Furthermore, APD 20 and APD 50 were shorter compared to WT, while APD 90 was similar. This in parts is consistent with previous data obtained from cardiomyocytes overexpressing HCN2 37 , which showed that outward tail current of I f shortened APD at membrane potentials more positive than reversal potential (~−35 mV for HCN4 38 ), while inward tail current of I f prolonged APD at membrane potentials more negative than reversal potential. However, prolongation of APD 90 was not observed in our model, most likely due to the repolarizing driving force of the electrogenic ‘reverse mode’ NCX, known to effectively shorten AP duration when [Na + ] i is increased 39 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, APD 20 and APD 50 were shorter compared to WT, while APD 90 was similar. This in parts is consistent with previous data obtained from cardiomyocytes overexpressing HCN2 37 , which showed that outward tail current of I f shortened APD at membrane potentials more positive than reversal potential (~−35 mV for HCN4 38 ), while inward tail current of I f prolonged APD at membrane potentials more negative than reversal potential. However, prolongation of APD 90 was not observed in our model, most likely due to the repolarizing driving force of the electrogenic ‘reverse mode’ NCX, known to effectively shorten AP duration when [Na + ] i is increased 39 .…”
Section: Discussionsupporting
confidence: 93%
“…The transgenic mouse overexpressing HCN2 specifically in the heart reportedly showed tachycardia, but PR and QRS durations were not shortened (Oshita et al . ). At present, the reasons for these discrepancies remain unclear; electrophysiological mechanisms regulating conduction velocity in the CCS should be explored in future research.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, ion channel-associated proteins, mainly hyperpolarization-activated cyclic nucleotide-gated channel 4 (HCN4), are related to the diastolic depolarization process of SAN [7]. In vitro and in vivo studies of gene manipulation for rodent neonatal rat cardiomyocytes to restore the ectopic pacing region by overexpressing embryonic transcription factors and ion channel-associated proteins have been proved to be successful [812]. Kapoor et al have proved that Tbx18 was the most effective transcription factor with the ability to transform neonatal ventricular myocytes into SAN-like cells by transducing a panel of transcription factors individually, including Shox2, Tbx3, Tbx5, Tbx18, and Tbx20 [11].…”
Section: Introductionmentioning
confidence: 99%